Novel approach for CES1 genotyping: integrating single nucleotide variants and structural variation. (March 2018) - Bjerre, Ditte; Berg Rasmussen, Henrik; INDICES Consortium, The
Aim: Development of a specific procedure for genotyping of CES1A1 ( CES1 ) and CES1A2, a hybrid of CES1A1 and the pseudogene CES1P1 .Materials & methods: The number of CES1A1 and CES1A2 copies and that of CES1P1 were determined using real-time PCR. Long range PCRs followed by secondary PCRs allowed sequencing of single nucleotide variants in CES1A1 and CES1A2 .Results & conclusion: A procedure consisting of two main steps was developed. Its first main step, the copy number determination, informed about presence of CES1A2 . This information enabled choice of PCR in the second main step, which selectively amplified CES1A1 and, if present, also CES1A2, for subsequent sequencing. Examination of 501 DNA samples suggested that our procedure is specific with potential for personalization of drug treatments.